Recorded music and practices of remembering - Anderson, Ben (Social & cultural geography, 2004)
Despite a resurgence of work that has begun to examine critically the artefactual mediation of memory, very few accounts have focused upon the interconnections between recorded music and daily acts of remembering. Drawing upon in-depth case study-based research into recorded music and everyday life with seventeen lower middle-class households, this paper describes the composition of three practices of remembering with and through recorded music. First, remembering how to choose and 'fit' specific purchased music to particular socio-spatial activities: a creative practice of mimicry, discretion and intuition in which the past is both embodied in the actions of judgement and choice and also functions to compose a co-present, but not-yet 'virtual' realm. Second, the widespread, ephemeral and subject-less practice of 'involuntary remembering' in which a trace of a virtual past affects 'in itself'. Finally, 'intentional remembering' in which a past is conditioned to occur as a fixed, relatively durable 'memory'. The paper describes how such practices of remembering are bound up with the emergence of domestic time-space, and thus the mode of being of the past, via the circulation and organization of affect.